2010
DOI: 10.1080/00288231003606351
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two management options to improve the water quality of Lake Brunner, New Zealand

Abstract: Lake Brunner, located on the west coast of the South Island of New Zealand, has been identified as threatened by phosphorus (P) inputs from neighbouring dairy farms. A two-year study was undertaken to determine if the application of reactive phosphate rock (RPR) with or without the addition of aluminium (Al) sulphate (alum) at 20 kg Al ha (1 could decrease P losses in surface runoff from dairy pastures compared to the same rate of P applied as superphosphate (30 kg P ha (1 ). The study was conducted on nine hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
(26 reference statements)
1
10
0
Order By: Relevance
“…Predicted and measured losses of TP in the Inchbonnie catchment (Table 5) were broadly similar to a mean yield of 8.2 kg P ha À1 year À1 reported for a field study of surface runoff close to this study site (McDowell 2010). The large losses of P for the Inchbonnie catchment (compared with dairy farms outside of the West Coast region) can be attributed to the combination of high source and transport risk factors for P loss from the dairy farms.…”
Section: Surface Water-groundwater Interactionsupporting
confidence: 51%
See 1 more Smart Citation
“…Predicted and measured losses of TP in the Inchbonnie catchment (Table 5) were broadly similar to a mean yield of 8.2 kg P ha À1 year À1 reported for a field study of surface runoff close to this study site (McDowell 2010). The large losses of P for the Inchbonnie catchment (compared with dairy farms outside of the West Coast region) can be attributed to the combination of high source and transport risk factors for P loss from the dairy farms.…”
Section: Surface Water-groundwater Interactionsupporting
confidence: 51%
“…Unfortunately, the general rule of applying P fertiliser when the likelihood of surface runoff, and hence P losses, is low is not possible in the Lake Brunner catchment. However, some evidence suggests that the use of a low-water-soluble P product may decrease P losses (compared with a highly water soluble P fertiliser) if surface runoff occurs soon after application (McDowell 2010).…”
Section: Dairy Farming and Lake Brunnermentioning
confidence: 99%
“…Only one study thus far has examined the efficacy of a surface application of alum (40 kg Al ha -1 ) to grazed dairy pasture. This study showed that in a high-rainfall environment (>4500 mm yr -1 ), alum sprayed onto pastures as a liquid did not decrease P losses (McDowell, 2010). It was hypothesized that alum had been washed off the soil surface in frequent runoff events before it could interact with the soil.…”
Section: Introductionmentioning
confidence: 84%
“…However, particularly in New Zealand, where intensive pastoral agriculture has expanded into areas of increased risk for P exports (i.e., greater slope, poorer soil P sorption), the adverse consequences of inappropriate selection of the form, placement, rate, and timing of P fertilizer applications are increasing. For example, fertilizer selection is important in situations where there is regular and frequent rainfall (McDowell, 2010), poor soil P sorption (McDowell and Monaghan, 2015), high hydraulic fluxes (Simmonds et al, 2015), or soil properties (e.g., acid soil pH) that result in the rapid dissolution of calcium phosphates (Simmonds et al, 2016). …”
Section: Implications For Fertilizer Good Management Practicesmentioning
confidence: 99%
“…Fertilizer selection is likely to be more important where there is frequent (e.g., >50 overland flow events) and reliable (e.g., >4000 mm rainfall annually) year‐round rainfall (McDowell, 2010), the soils are hydrophobic (Simmonds et al, 2017), or there are accidental additions of fertilizer‐P to stream channels from aerial applications in steeper country (McDowell et al, 2010). In those instances, sparingly soluble or slow release fertilizer could well be the most appropriate, providing the agronomic objectives for its application are achieved.…”
Section: Implications For Fertilizer Good Management Practicesmentioning
confidence: 99%